Load shifting potential assessment of building thermal storage performance for building design. (15th March 2022) - Ding, Yan; Lyu, Yacong; Lu, Shilei; Wang, Ran
Abstract: As major energy consumers, buildings have great potential to alleviate the imbalance between renewable energy generation and consumer demand. A building thermal mass is a free energy storage object, and can provide a load shifting capacity. In this study, a parameter denoted the 'effective thermal capacitance' was proposed to characterise the building thermal mass, and a reduced-order RC model was established to predict the building cooling and heating loads. By using the particle swarm optimisation algorithm to identify the effective thermal capacitance values, the linear relationships between the effective thermal capacitance and building areas were summarised. The results show that, with an increase in the effective thermal capacitance, the hourly load and energy losses caused by load shifting strategies decrease. According to comparison results from applying the preheating and precooling strategies in four climatic zones of China, it is found that although the total load throughout the day is increased, the peak electricity consumption can be shifted without noticeable changes in the daily electric bill. During office hours, the preheating strategy reduces the heating load by approximately 12% in the severe cold and cold zones, whereas precooling reduced the cooling load by 20%–45% in all four climatic zones. Highlights: Cooling/heating loads are predicted for building designs by a reduced-order RC model. A load shifting capacity can be represented by the effective thermal capacitance. The load shifting potentials in different climate zones of China are illustrated.